Times Are Harsh, Be Kind to Yourself! Anxiety, Life Satisfaction, and the Mediating Role of Self-Compassion - Maftei, Alexandra; Lãzãrescu, Georgiana (Frontiers in Psychology, 2022)
The present research aimed to explore the indirect effect of self-compassion on the relationship between two dimensions of intolerance of uncertainty (i.e., prospective and inhibitory anxiety) and life satisfaction. One hundred sixty-four Romanian adult participants formed our sample from the country's eastern side. Their ages ranged between 18 to 61 (M = 23.45, SD = 7.70, 72% females). The study was conducted in 2021, when the Delta wave of Covid-19 was at its peak. Our findings suggested significant negative associations between prospective anxiety, self-compassion, and life satisfaction. A similar negative significant association was suggested between inhibitory anxiety and self-compassion. Age did not significantly correlate with any of our primary variables. Mediation analyses indicated a total mediating effect of self-compassion on the relationship between participants' prospective and inhibitory anxiety and their life satisfaction. We discuss the implications of our findings, considering their relevance for therapeutical interventions aimed to promote psychological well-being when facing adversity.